Barths "Tambacher Vortrag" und Bonhoeffers "tiefe Diesseitigkeit": bahnbrechende Impulse für Kirche und Gesellschaft noch heute - Welker, Michael (Evangelische Theologie, 2019)
This paper examines two ingenious theological contributions by Karl Barth and Dietrich Bonhoeffer: the famous Tambach lecture by Barth, given 100 years ago, and the concept of the »deep worldliness« (tiefe Diesseitigkeit) of the Christian faith developed by Bonhoeffer in his prison letters. It shows why even today both contributions have orienting power for church and society in situations of radical transition and change. Both contributions derive their strength from the fact that they have a clear theological and at the same time realistic orientation, Christologically and implicitly also pneumatologically founded. On this base they link a serious theology and a vigilant critical contemporaneity.
Keywords: Diesseitigkeit; Christentum; Bonhoeffer, Dietrich; Mensch; Gott; Gesellschaft; Jesus Christus; Barth, Karl / Der Christ in der Gesellschaft